TEXTURE DEVELOPMENT OF CALCITE BY DEFORMATION AND DYNAMIC RECRYSTALLIZATION AT 1000K DURING TORSION EXPERIMENTS OF MARBLE TO LARGE STRAINS - Pieri M.; Kunze K.; Burlini L.; Stretton I.; Olgaard D.L.; Burg J.P.; Wenk H.R. (My University, 2001)
Torsion deformation experiments were performed on solid cylinders of Carrara marble at high temperature (1000 K) and constant twist rate (about 4×10⁻⁴ rad s⁻¹) to large twist angles (between 80° and 840°). These conditions correspond to simple shear deformation at constant shear strain rate (3×10⁻⁴ s⁻¹) and variable amounts of shear strain γ of 1, 2, 5 and 11 at the outer mantle of the sample cylinders. Lattice preferred orientations (LPO) were measured on polished thin sections using automated electron backscatter diffraction (EBSD) to analyze the microtextures in orientation imaging micrographs (OIM).